(untitled) (Far Western Review, 2025)
Qualitative research aims to understand and interpret language, language learning or use in specific contexts, as well as social phenomena, within natural settings like social and school environments. This study explores the practices of doing literature reviews in qualitative research and also provides practical insights for fellow researchers in qualitative research fields. This study explores the practices of doing literature reviews in qualitative research and provides insights for practically conducting researches for fellow researchers in qualitative fields. The article analyzes ten different articles from Scopus-indexed journals, The Qualitative Report (TQR), and the International Journal of Qualitative Methods (IJQM), published between 2010 and 2023. I followed Braun & Clarke’s framework of thematic analysis to analyze the secondary data in the selected articles. Based on the articles, I analyze the approaches, practices, and challenges in conducting qualitative literature reviews. The study educates that the qualitative literature reviews show methodological diversity, including thematic analysis, context-specific frameworks, and innovative practices like narrative construction and alternative data management strategies. Trustworthiness and rigor are emphasized through credibility, dependability, and confirmability to ensure ethical and methodological integrity. Pedagogical applications further demonstrate the educational relevance of these approaches. Qualitative literature reviews exhibit theoretical richness, methodological rigor, narrative depth, and practical innovation, making them valuable tools for bridging theory and practice in the growing field of qualitative research